Enhancement and Innovation in Higher Education in Nigeria through Technical Vocational Education and Training (TVET) and Entrepreneurship Education - Okoye, K. R. E.; Okwelle, P. C; Okoye, P. I. (Advances in Social Sciences Research Journal, 2015)
It is well reported that one of the factors that plague higher education system in Nigeria is lack of intrigue to discover an innovative effort that should bear on research and development, thus the backwardness of Nigeria among the comity of highly developed nations globally. Widely reported also, is that effort to implicate innovative discoveries among students through research and development (R & D) is not given the desired attention in Nigerian higher institutions. With mind cast on a possible situation that the world economy could be submerged into catastrophic social vices, Technical Vocational Education and Training (TVET) with its entrepreneurship component, has been acclaimed a system that could circumvent the eventual odd. In this paper, need for creative empowerment through TVET and entrepreneurship education for creativity and innovation were considered; with emphasis on indicator factors to global economy. The paper concludes that to join in the bandwagon of improved economy, stakeholders in Nigerian education must not neglect TVET education.